HIF-1α Directly Controls WNT7A Expression During Myogenesis - Cirillo, Federica; Resmini, Giulia; Angelino, Elia; Ferrara, Michele; Tarantino, Adriana; Piccoli, Marco; Rota, Paola; Ghiroldi, Andrea; Monasky, Michelle M.; Ciconte, Giuseppe; Pappone, Carlo; Graziani, Andrea; et al. (Frontiers in Cell and Developmental Biology, 2020)
Herein we unveil that HIF-1α directly regulates WNT7A expression during myogenesis. In fact, chromatin immunoprecipitation and site-directed mutagenesis experiments revealed two distinct Hypoxia Response Elements (HREs) that are specific HIF-1α binding sites on the WNT7A promoter. Remarkably, a pharmacological activation of HIF-1α induced WNT7A expression and enhanced muscle differentiation. On the other hand, silencing of WNT7A using CRISPR/Cas9 genome editing blocked the effects of HIF-1α activation on myogenesis. Finally, treatment with prolyl hydroxylases inhibitors improved muscle regeneration in vitro and in vivo in a CTX-induced muscle injury mouse model, paving the way for further studies to test its efficacy on acute and chronic muscular pathologies.